Efficient determination and evaluation of steady-state thermal-mechanical variables generated by wire arc additive manufacturing and high pressure rolling - Gornyakov, Valeriy; Sun, Yongle; Ding, Jialuo; Williams, Stewart W. (IOP Publishing, 2021)
Wire arc additive manufacturing (WAAM) of large component is susceptible to residual stress (RS) and distortion, which are detrimental and need to be mitigated through high pressure rolling or other methods. In this study, an efficient modelling approach is developed to simulate both WAAM and rolling, and this approach can also be applied to other manufacturing processes to determine steady-state variables. For a clamped wall component, the computationally efficient reduced-size WAAM and rolling models (i.e. short models) can obtain steady-state solutions equivalent to those obtained by conventional full-size models. In the short models, the undesirable effect of reducing the length of the modelled component is counteracted by imposing additional longitudinal constraint as proper to specific processes. The steady-state solution obtained by the short model in clamped condition is then mapped to a long model for analysis of RS and distortion after removal of clamps. The WAAM model predictions of temperature, RS and distortion are in good agreement with experimental measurements. For the steady-state region in the WAAM deposited wall, compressive longitudinal plastic strain (PS) is approximately uniformly formed, and the influential factors and implications of the PS are analysed. The high pressure rolling on the wall after WAAM deposition introduces tensile PS that compensates for the compressive PS induced by the WAAM deposition, thereby mitigating the tensile RS in the clamped wall and alleviating the bending distortion after the removal of clamps. This study demonstrates an efficient approach for modelling large-scale manufacturing and provides insights into the steady-state strains and stresses generated by WAAM and rolling.
Keywords: Large-scale additive manufacturing; rolling; residual stress; distortion; plastic strain; simulation